BULLOUS PAPULAR URTICARIA – CASE REPORT AND BRIEF REVIEW OF THE LITERATURE - Ássimos, Isabella; Pedrosa, Ana; Martins, Paulo; Bettencourt, Herberto; Azevedo, Filomena (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Papular urticaria (PU), also known as prurigo strophulus, is a relatively common skin disorder of chil- dhood caused by hypersensitivity to a variety of bites, including those of mosquitoes, fleas, bedbugs and others insects. It is characterized by a chronic or recurrent, papular or vesicobullous eruption, that is often pruritic and uncomfortable. The resultant scratching may lead to erosions and secondary pyoderma. Patients affected by these eruptions are frequently misdiagnosed and often subject to unnecessary, expensive and/or invasive evaluations. In order to avoid that, clinicians should be aware of the characteristic skin lesions of PU, possible exposures, and natural history of the disease. The most challenging aspects of PU is convincing parents/patients that the lesions are related to a bite reaction, demystify the common belief of the relationship with the ingestion of certain foods, and identifying and eradicating the source of the offending insect. We herein describe a 25-year-old female patient with bullous PU, and present a brief review of the literature, including the clinical features, utility of mnemonic “SCRATCH” to aid clini- cians in making an early and accurate diagnosis, differential diagnoses, and 3 “P’s” of therapy (Prevention, Pruritus control, and Patience). KEYWORDS – Skin diseases, vesiculobullous; Urticaria; Prurigo; Criança; Insects.